THE INFLUENCE OF WORK MOTIVATION, DISCIPLINE AND WORK ENVIRONMENT ON ASN PERFORMANCE WITH WORK COMPENSATION INTERVENING VARIABLES IN WEST PASAMAN HOSPITAL - Syartika, Jelli Isma; Elfiswandi, Elfiswandi; Zefriyenni, Zefriyenni (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
This research aims to determine the influence of work motivation, discipline and work environment on ASN performance through work compensation as an intervening variable at West Pasaman Regional Hospital. The method used is multiple linear regression analysis and path analysis. by distributing a questionnaire to 100 respondents. The results obtained show that there is a positive and significant influence of work motivation on work recovery. There is a positive and insignificant influence of discipline on work compensation. There is a positive and insignificant influence of the work environment on work compensation. There is a positive and significant influence of work motivation on performance. There is a positive and significant influence of discipline on performance. There is a positive and significant influence of the work environment on performance. There is a positive and insignificant effect of work recovery on performance. Work pay does not mediate the effect of work motivation on performance. Work compensation does not mediate the influence of the work environment on performance. Finally, the author suggests to the West Pasaman Regional Hospital to further increase work motivation, discipline and pay attention to the work environment so that it is hoped that employee performance will increase. Keywords: Work Motivation, Discipline, Work Environment, Compensation and Performance